Cultural impact of Counselling: An Indian Case Study - Devayani Kashyap (Academia Edu Cendekia Indonesia (AEDUCIA), 2025)
Background: The cultural impact on counseling is increasingly relevant in diverse societies, such as India, where traditional values intersect with modern influences. Understanding cultural differences is crucial for improving therapeutic outcomes. This study examines how cultural values influence the counseling process, using the example of Arjun from the Bhagavad Gita. Objective: The study aims to examine the cultural impact on counseling by analyzing how Western counseling models can be adapted to the Indian context, integrating indigenous cultural perspectives, and evaluating the effectiveness of culturally sensitive approaches. Method: This study employs a case study approach to analyze the counseling interaction between Lord Krishna and Arjuna in the Bhagavad Gita. Data was collected from the text and supplemented by literature on multicultural counseling and psychological theories. The data was analyzed qualitatively using thematic analysis. Result: The findings show that integrating cultural traditions can enhance therapeutic effectiveness. The case study demonstrates that culturally relevant interventions can address psychological challenges in diverse cultural contexts. Conclusion: Integrating cultural values into counseling practices improves the relevance and effectiveness of interventions, particularly in India. This study emphasizes the significance of cultural competence in counseling, enabling counselors to more effectively address the diverse needs of clients from various backgrounds. Contribution: The study contributes insights into the integration of cultural practices in counseling, emphasizing the need for cultural competence training for counselors.